2014
DOI: 10.5812/archneurosci.21529
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Iranian men With Spinal Cord Injury in Comparison With General Population

Abstract: Background: Spinal cord injury (SCI) imposes a tremendous burden on physical, mental and psychosocial aspects of life among affected individuals. Objectives: Until now, there was no statistics about the quality of life (QoL) in Iranian males with SCI. Here, we assessed the QoL among Iranian men with SCI and compared it with general population. Patients and Methods: Referred male patients with SCI to Brain and Spinal Injury Research Center (BASIR) were invited to participate in this investigation. The QoL was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The SCI makes patients vulnerable to experiencing lifetime secondary clinical problems that may lead to impairments in their health, wellbeing, social, and career activities (2). People with SCI are faced with motor impairments, loss of bladder or bowel control, sexual problems, pressure ulcers, and chronic pains that negatively impact their psychosocial functioning (3,4). About 90 million people around the world suffer from SCI, with motor vehicle accidents, falls, and gunshot wounds being the leading causes worldwide (3).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCI makes patients vulnerable to experiencing lifetime secondary clinical problems that may lead to impairments in their health, wellbeing, social, and career activities (2). People with SCI are faced with motor impairments, loss of bladder or bowel control, sexual problems, pressure ulcers, and chronic pains that negatively impact their psychosocial functioning (3,4). About 90 million people around the world suffer from SCI, with motor vehicle accidents, falls, and gunshot wounds being the leading causes worldwide (3).…”
Section: Contextmentioning
confidence: 99%
“…Medical advances in recent years have improved the life expectancy of people with SCI (7). Despite these medical advances, the efforts in this area are not only focused on increasing the patients' life expectancy, but the main challenge is to improve the people's quality of life (QOL), as chronic disorders have well-known negative impacts on people's QOL (4,8). Health-related quality of life (HRQoL) is a subjective measure that includes the subject's current health status, available health care services, and health improving activities (9).…”
Section: Contextmentioning
confidence: 99%
“…[ 9 10 11 12 ] Some studies on the QOL of PWDs have been undertaken in Iran, and the findings reveal that a relatively substantial number of Iranians with physical impairments are unemployed. [ 13 14 ] According to Pawłowska et al .,[ 15 ] work has a substantial impact on the psychological fulfillment and overall health of PWDs aged 18 to 65 years. Their research also found that the QOL of PWDs who were jobless and not seeking employment declined as professional inactive duration increased.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Haddadi et al, it was equal to 906 patients (3), which is a prominent amount. This disease can reduce function, cause pain, decrease quality of life, sexual dysfunction, and cause pressure ulcers (6)(7)(8). Other problems that appears with SCI include post-traumatic stress disorder, osteoporosis, orthostatic hypotension, and auto-reactive disorders (9,10).…”
Section: Introductionmentioning
confidence: 99%